(untitled) (Theological Kronos, 2021)
The concept of “Poor” in Leonardo Boff, the social and theological reality that many live, the discourse of the theology of prosperity and the concept of Aporophobia proposed by Professor Adela Cortina, are important aspects for the development of this work. Therefore, initially a clearer identification of the subject of the reference is expected and of the effects of the discourse, they receive from the ministries that practice this way of doing theology. To achieve this interpretative objective, three moments will address; the first one alludes to the way in which Leonardo Boff has approached the concept of “poor”. The second moment revolves around the innovative identification proposal of Professor Adela Cortina against the invisibility of the poor, and a third in which Michel Foucault’s approach introduces to understand the discourse of the theology of prosperity.